EFEKTIVITAS PENGGUNAAN MEDIA DIORAMA DALAM PEMBELAJARAN MENULIS DESKRIPSI DI KELAS III SEKOLAH DASAR - , YANA; ISNAINI DAMAYANTI, MARYAM (Jurnal Penelitian Pendidikan Guru Sekolah Dasar, 2018)
Abstract This study aims to determine the effectiveness of the use of diorama media in learning to write a description in the third grade of elementary school of Lidah Kulon IV Surabaya. The design of this research is Pre-Experimental Design. The Pre-Experimental design form used is the One-Group Pretest-Posttest Design. The sample of the research is the students of grade IIIB elementary school Lidah Kulon IV Surabaya which has 24 students. Data collection techniques uses observation techniques, learning techniques, and student motivation questionnaire. The result of research shows that the average pretest value is 62,70 while the result of posttest average value is 80,83. Based on hypothesis test calculation, obtained is 8.32 ? 2.069 so Ha accepted and Ho rejected. Thus, it can be concluded that the use of diorama media is effective in learning to write descriptions. Keywords: diorama media, write description.